PENILAIAN KONSEP GREEN BUILDING PADA GEDUNG LABORATORIUM TERPADU INSTITUT TEKNOLOGI KALIMANTAN SESUAI STANDAR GREENSHIP 1.2 - Oryza Lhara Sari; Andika Ade Indra Saputra; Naila Anisa Dwigida Aprilla (LPPM Universitas Abdurrab, 2023)
In the City of Balikpapan, the number of buildings that apply the green building concept and are certified according to the green building certification data still does not exist. Sustainable development at the Kalimantan Institute of Technology (ITK) is one of the largest in East Kalimantan. The development will have an impact on changes in environmental conditions. The application of the green building concept to the ITK building is expected to reduce the negative impact on environmental change. The focus of this research case study is the ITK Integrated Laboratory Building. The thing being reviewed is the application of green building in the ITK Integrated Laboratory building using the calculation parameters on Greenship for New Buildings Version 1.2. The method that will be used in this research is to evaluate the application of green building in the ITK Integrated Laboratory Building. The evaluation value of the application of green building in the ITK Integrated Laboratory building is 9.08 points or 8.99% which does not meet the requirements for implementing green building in accordance with the greenship 1.2 standard.